A new species of tadpole-goby, Benthophilus persicus sp. nov. (Teleostei: Gobiidae) from the southern Caspian Sea - Kovačić, Marcelo; Esmaeili, Hamid Reza; Zarei, Fatah; Abbasi, Keyvan; Schliewen, Ulrich K. (Zootaxa, 2021)
A new gobiid species, Benthophilus persicus sp. nov., is described from the southern Caspian Sea, Iran. The new species is diagnosed by the following character states: dermal fold on cheek well-developed, large, rectangular; chin barbel 1/3–2/3 of eye diameter; maximum body width 15.1–22.9% of standard length; mouth width, 36.3–55.8% of head length; second dorsal fin I+7–8; origin of anal fin in front of vertical through origin of second dorsal fin; dermal tubercles present on body, clearly larger than granules, with two posterior rows of spinules forming an acute angle, always less than right angle; dorsal row of tubercles complete, 22–29; ventral row of tubercles 22–25; ventrolateral row of tubercles absent; tubercles not present on temporal and occipital head regions; granules not present on flanks; transversal suborbital row 6i below posterior end of row b; anterior interorbital transversal row pa with one or two papillae and anterior interorbital transversal papilla row pp with two or three papillae; body with 20–22 transversal ltm rows starting anteriorly behind pectoral axilla and alternating anteriorly with three longitudinal llm rows.